Folklore and Crime: Models and Applications of Research - Conn, Joel (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2019)
The folklore related to crime and its perpetrators forms a diverse body of lore. This paper proposes that this variation arises principally from the different actors and their interaction. A method of examination is set out that considers which folk group is telling or practicing the folklore and in relation to which group it is told or practiced (such as victims about perceived perpetrators; or accused about the judiciary). This is followed by a general examination of folklore within these categories before undertaking a case study of a large body of folklore regarding a single form of crime (Advance Fee Fraud, also known as the “419” or “Nigerian Prince” scam).